Acrolein and other toxicant exposures in relation to cardiovascular disease among marijuana and tobacco smokers in a longitudinal cohort of HIV-positive and negative adults. (January 2021) - Lorenz, David R.; Misra, Vikas; Chettimada, Sukrutha; Uno, Hajime; Wang, Lanqing; Blount, Benjamin C.; De Jesús, Víctor R.; Gelman, Benjamin B.; Morgello, Susan; Wolinsky, Steven M.; Gabuzda, Dana
Abstract: Background: Marijuana smoke contains some of the same toxicants present in tobacco smoke. Marijuana smoking is prevalent among HIV+ individuals, but few studies have characterized smoke-related toxicants or associated health outcomes in exclusive marijuana users. Methods: This longitudinal study included 245 participants over age 40 (76% HIV+). 33 plasma and 28 urine metabolites of nicotine, ∆-9-trans-tetrahydrocannabinol, polycyclic aromatic hydrocarbons, and volatile organic compounds were assayed by liquid or gas chromatography/mass spectrometry. Exposures and health outcomes were assessed from surveys and medical records. Findings: At baseline, 18% of participants were marijuana-only smokers, 20% tobacco-only smokers, and 24% dual marijuana-tobacco smokers (median (IQR) age 53 (47–60) years, 78% male, 54% white race). Marijuana smoking was independently associated with elevated plasma naphthalenes, 2-hydroxyfluorene sulfate, 4-vinylphenol sulfate, and o-cresol sulfate (p< 0·05) and urine acrylonitrile and acrylamide metabolites ( p< 0·05), but levels were lower than those associated with tobacco smoking. Acrolein metabolite N-Acetyl-S-(3-hydroxypropyl)-l -cysteine (3HPMA) was significantly elevated in plasma and urine in tobacco-only and dual but not marijuana-only smokers, and correlated with nicotine metabolites ( p< 0·05). The highest tertile of 3HPMA was associated with increased cardiovascular disease diagnoses independent of tobacco smoking, traditional risk factors, and HIV status (odds ratio [95% CI] 3·34 [1·31–8·57]; p = 0·012). Interpretation: Smoke-related toxicants, including acrylonitrile and acrylamide metabolites, are detectable in exclusive marijuana smokers, but exposures are lower compared with tobacco or dual smokers. Acrolein exposure is increased by tobacco smoking but not exclusive marijuana smoking in HIV+ and HIV- adults, and contributes to cardiovascular disease in tobacco smokers. Funding: U.S. NIH.